Research Challenges of Studies on Crimes against Archaeological Heritage in Poland - Mroczek, Diana (Sensus Historiae, 2023)
The article analyses the challenges of investigating crimes against archaeological heritage in Poland, in particular the activities of illegal treasure hunters. Despite the efforts of the government, law enforcement and cultural heritage experts, such criminal activities are becoming more frequent and serious, which results in the loss of valuable information and the artefacts themselves. The article examines the causes of these problems, including the lack of effective legal protection, inadequate monitoring and limited public awareness of national heritage. It also contains recommendations for better communication between archaeologists and treasure hunters as well as emphasizes the need for decisive action to protect Poland’s archaeological heritage.